Pengaruh Labelisasi Halal dan Harga terhadap Loyalitas Pelanggan dalam Pembelian Produk Skincare Wardah (Studi Kasus Santri Pondok Pesantren Banyuanyar) - Hofifah; Q, Siti Ramdlaniyatul; Fata, Zainol; Magfiroh, Saodatul (AL-UJRAH, 2025)
Absract Indonesia is the country with the largest Muslim population in the world, making it a highly promising market, including in the skincare sector which has become a current trend. This is supported by the rapid development of technology that helps the marketing world grow quickly, inspiring people to pay more attention to their appearance. This study aims to determine the effect of X1 halal labeling and X2 price on X3 loyalty in Y the purchase decision of Wardah skincare among active female students at Banyuanyar Islamic boarding school in the year 2025. The research method used is a quantitative approach, as the data is in the form of numerical values and analyzed using statistical tools. The population in this study is Wardah skincare users among active female students at Banyuanyar. A sample of 100 respondents was selected using nonprobability sampling with a purposive sampling approach. The data were analyzed using SPSS. The results of the study show that the halal labeling variable has a partial positive effect Keywords: Halal Labeling, Price, Loyalty, Purchase Decision